2016
DOI: 10.1186/s41240-016-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and in vitro culture of primary cell populations derived from ovarian tissues of the rockfish, Sebastes schlegeli

Abstract: This study was conducted to identify the general conditions for the isolation and in vitro culture of ovary-derived cells in rockfish (Sebastes schlegeli). The effects of three different enzymes on cell retrieval from ovarian tissues were evaluated first, and then the ovary-dissociated cells were cultured under various culture conditions, with varying basal media and culture temperatures, addition of growth factors, and/or culture types. We found that collagenase type I treatment was effective for cell isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Cell growth was observed at all temperatures tested. Similar results were observed by Ryu et al (2016) when ovarian cells were dissociated and cultured from rockfish, Sebastes schlegeli . Ryu et al (2016) grew cells at 15°C, 20°C, and 25°C.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Cell growth was observed at all temperatures tested. Similar results were observed by Ryu et al (2016) when ovarian cells were dissociated and cultured from rockfish, Sebastes schlegeli . Ryu et al (2016) grew cells at 15°C, 20°C, and 25°C.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were observed by Ryu et al (2016) when ovarian cells were dissociated and cultured from rockfish, Sebastes schlegeli . Ryu et al (2016) grew cells at 15°C, 20°C, and 25°C. We found that primary cells consisted of a heterogenous population of epithelial and fibroblast‐like cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…But, in some cases like testis tissues, they are cultured in less than 37°C based on the anatomic difference (Gohbara et al, 2010). In contrast to mammalian species, however, fish can acclimate to a wide range of temperature as a poikilothermic vertebrate and thus the cultured cells from fish can also tolerate a wide range of temperature (Lannan et al, 1984;Qin et al, 2006;Ryu et al, 2016). However, it has been reported that the alteration of temperature in culture of fish cells is able to influence the physiology of the cells (Lannan et al, 1984).…”
Section: Discussionmentioning
confidence: 99%